To recruit and advance : women students and faculty in science and engineering (National Academies Press, 2006)
Although more women than men participate in higher education in the United States, the same is not true when it comes to pursuing careers in science and engineering. To Recruit and Advance: Women Students and Faculty in Science and Engineering identifies and discusses better practices for recruitment, retention, and promotion for women scientists and engineers in academia. Seeking to move beyond yet another catalog of challenges facing the advancement of women in academic science and engineering, this book describes actions actually taken by universities to improve the situation for women. Serving as a guide, it examines the following: Recruitment of female undergraduate and graduate students; Ways of reducing attrition in science and engineering degree programs in the early undergraduate years; Improving retention rates of women at critical transition points from undergraduate to graduate student, from graduate student to postdoc, from postdoc to first faculty position; Recruitment of women for tenure-track positions; Increasing the tenure rate for women faculty; and, Increasing the number of women in administrative positions. This guide offers numerous solutions that may be of use to other universities and colleges and will be an essential resource for anyone interested in improving the position of women students, faculty, deans, provosts, and presidents in science and engineering.